Smoking in Malaysia: Main issues and ways to overcome - Mohammed Nawi, Azmawati; Jetly, Kavita; Ramli, Nur Suhada (IIUM Medical Journal Malaysia, 2021)
Smoking is a public health problem worldwide and in Malaysia. According to serial Malaysian data, the age of initiation of smoking are at a younger age and the prevalence of smoking in Malaysia among adults and adolescents have not reduced much over the years. Smoking has a detrimental heath effect to smokers as well as those passively smoking. Younger age of smoking is linked to increased dependence of nicotine and many other high-risk behaviours. The two main issues which is addressed here is younger age of initiation of smoking and smoking bans in Malaysia. The factors which contribute to younger age of smoking initiation is tobacco factors, school factors, family factors and social factors. Challenges to smoking bans in Malaysia includes poor enforcement and innovation of tobacco products in Malaysia. A comprehensive approach including the mPOWER strategy should be carried out to address this problem towards achieving Tobacco Endgame.